دور البيئة اللغوية في اكتساب مهارة الكلام في معهد دار النون الإسلامي مالانج - Fikri, Alvian Izzul (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2024)
The research aims to describe the role of the linguistic environment in acquiring speaking skills among students at the Dar Al-Nun Islamic Institute, Malang. The linguistic environment plays a significant role in helping students at the institute develop their speaking abilities. Indicators of improvement in students' speaking skills are observed through their communication proficiency. After analyzing the results of this qualitative study using the Miles and Huberman method, the research reveals that the role of the linguistic environment in acquiring speaking skills can be categorized into three main aspects: (1) correcting incorrect language usage, (2) enhancing and expanding linguistic knowledge, and (3) influencing the frequency and success of acquiring speaking skills. These roles are realized through various student activities aimed at improving speaking skills, such as presenting vocabulary and synonyms, engaging in conversations, celebrating Language Day, participating in lectures or dialogues with native speakers, and expressing opinions.